A convenient route to symmetrically and unsymmetrically substituted 3,5-diaryl-2,4,6-trimethylpyridines via Suzuki–Miyaura cross-coupling reaction - Błachut, Dariusz; Szawkało, Joanna; Czarnocki, Zbigniew (Beilstein Journal of Organic Chemistry, 2016)
A series of differently substituted 3,5-diaryl-2,4,6-trimethylpyridines were prepared and characterized using the Suzuki–Miyaura coupling reaction with accordingly selected bromo-derivatives and arylboronic acids. The reaction conditions were carefully optimized allowing high yield of isolated products and also the construction of unsymmetrically substituted diarylpyridines, difficult to access by other methods.
Keywords: arylpyridines; cross coupling reaction; heteroaromatics; one-pot reaction; palladium catalyst